The Quantifying the Relationship Between ENSO-Induced SST Anomalies and Rainfall Variability in East Java’s Coastal Regions - Hasibuan, Muhammad Ansori; Shidiq, Ilham Abdullah; Asifin, Hasyid Agha Zuhairul; Sa’diyah, Qosinatus; Giarno (Universitas Negeri Semarang, 2024)
El Nino and La Nina events affect the conditions of the rainy season and dry season, especially as a cause of flooding in coastal areas. The North Coast of Java is a coastal area that is prone to disasters due to the influence of sea level anomalies caused by the interaction of the sea and the atmosphere. The northern coast of East Java, which is directly adjacent to the coast, has a high level of vulnerability to tidal flooding or rob disasters. This study aims to examine the effect of the Nino 3.4 index on the El Nino and La Nina phases in influencing rainfall on the northern coast of East Java, especially in the areas of Tuban, Lamongan, Gresik, Surabaya City, Sidoarjo, Pasuruan, Probolinggo, and Situbondo. The method used is a correlation analysis between rainfall parameters and the Nino3.4 index to determine the relationship between parameters. The results of the study on La Nina, El Nino, and Neutral conditions have a negative relationship in almost all research locations with moderate to very low correlation values. This study provides an explanation of the relationship between rainfall and ENSO to flooding events on the northern coast of East Java.